Growth shapes of supported Pd nanocrystals on SrTiO3 (001) - Silly, F; Powell, A; Martin, M; Castell, M (American Physical Society, 2005)
Pd is deposited onto a reconstructed SrTiO3 (001) substrate in an ultrahigh vacuum environment. Elevated substrate temperature during or following deposition causes epitaxial Pd nanocrystals to form. The nanocrystal shape and size distributions are analyzed by scanning tunneling microscopy. We find that depending on substrate reconstruction and substrate temperature during deposition three shapes of nanocrystal are obtained: truncated pyramids, huts, and hexagonal shaped disks. In our previous study [F. Silly and M. R. Castell, Phys. Rev. Lett. 94. 046103 (2005)] the energetics of the equilibrium nanocrystal shapes were analyzed. Here we report on the nonequilibrium growth shapes. We show that preferential growth for huts is along their (001) end facets. For hexagons growth proceeds by attachment to the side of the crystals. Truncated pyramids can grow preferentially along one of their (111) side facets resulting in an elongated shape.